Impaired High‐Density Lipoprotein Function in Patients With Heart Failure - Emmens, Johanna E. (J Am Heart Assoc, 2021)
BACKGROUND: We recently showed that, in patients with heart failure, lower high‐density lipoprotein (HDL) cholesterol concentration was a strong predictor of death or hospitalization for heart failure. In a follow‐up study, we suggested that this association could be partly explained by HDL proteome composition. However, whether the emerging concept of HDL function contributes to the prognosis of patients with heart failure has not been addressed. METHODS AND RESULTS: We measured 3 key protective HDL function metrics, namely, cholesterol efflux, antioxidative capacity, and anti‐inflammatory capacity, at baseline and after 9 months in 446 randomly selected patients with heart failure from BIOSTAT‐CHF (A Systems Biology Study to Tailored Treatment in Chronic Heart Failure). Additionally, the relationship between HDL functionality and HDL proteome composition was determined in 86 patients with heart failure. From baseline to 9 months, HDL cholesterol concentrations were unchanged, but HDL cholesterol efflux and anti‐inflammatory capacity declined (both P<0.001). In contrast, antioxidative capacity increased (P<0.001). Higher HDL cholesterol efflux was associated with lower mortality after adjusting for BIOSTAT‐CHF risk models and log HDL cholesterol (hazard ratio, 0.81; 95% CI, 0.71–0.92; P=0.001). Other functionality measures were not associated with outcome. Several HDL proteins correlated with HDL functionality, mainly with cholesterol efflux. Apolipoprotein A1 emerged as the main protein associated with all 3 HDL functionality measures. CONCLUSIONS: Better HDL cholesterol efflux at baseline was associated with lower mortality during follow‐up, independent of HDL cholesterol. HDL cholesterol efflux and anti‐inflammatory capacity declined during follow‐up in patients with heart failure. Measures of HDL function may provide clinical information in addition to HDL cholesterol concentration in patients with heart failure.